Analisis faktor-faktor yang mempengaruhi profitabilitas perbankan - Idhiah Nurdianti; Mudhita Elviani; I Gusti Kade Birawan (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
Analysis of Factors Influencing the Profitability of Banking Sector Companies Listed on the IDX. Thesis, Management Study Program, Faculty of Economics, Business and Humanities, University of Tangerang Raya. The form of research used is a form of quantitative research. The sample in this research is 8 banks. The data used are primary data and secondary data. Data collection method through data ojk. Data analysis used is qualitative and quantitative analysis. The analysis technique uses the KMO technique. Based on the description that has been stated previously and based on the data obtained in connection with research activities carried out at BANK in Indonesia, the researcher can draw conclusions and provide suggestions that can be useful for the management in the problems faced by company. There are 3 factors affecting profitability seen from the company's Return on Assets (ROA) in Indonesian banking, namely: CAR NPL and NIM factors with eigenvalues of 29.909%, 19.939% and 17.806%. With 6 variable variances that correlate with the formed factors, namely: CAR, NIM, NPL, LDR, BOPO and ROA.